GOVERNMENTAL BRANDING AS STRATEGY TO BUILD PUBLIC'S TRUST, LOYALTY, AND PARTICIPATION - Bambang Sukma Wijaya (Journal Communication Spectrum, 2018)
Increasing public expectations requires government institutions to improve themselves. Like a brand, the government needs a unique, structured, and integrated strategy to focus more on the target. However, the main problems in communicating government-related values ​​are trust, loyalty, and participation. This challenge is usually due to the perception, reputation, and credibility constraints of the parties involved in government affairs. Thus, Governmental Branding is an effort by the government or government-related institutions to gain and increase public trust, participation, and loyalty through communication, activation, and amplification of governmental values related to citizens' needs, aspirations, problems, and interests. This article proposes how governmental branding can be systematically built to form a good perception, affection, and impression of government and its attributes to help communicate governmental values ​​well and reduce constraints and adverse effects. There are various dimensions and aspects related to governmental branding, namely 1) Behavioral Dimensions (ranging from public awareness to loyalty), 2) Managerial Dimensions (ranging from governance to efficiency), 3) Physical Dimensions (ranging from distinctive identity signifiers to resources and environmental issues), 4) Relational Dimensions (ranging from public relations to the private sector), 5) Sociocultural Dimensions (ranging from philanthropic efforts to community development), 6) Representational Dimensions (ranging from communication and dialog to constructive narratives), 7) Financial Dimensions (ranging from investment perception to debt), and 8) Political Dimensions (ranging from policies to political trust).